Analysis of Integrated Audit Approach in Auditing Sustainable Energy Development Programs in State-Owned Enterprises - Febrianto, Fernandus Roni; Amyar, Firdaus; Puspitasari, Ratih (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This research examines the use of the Integrated Audit Approach in auditing National Program 6, Sustainable Energy Development, on State-Owned Enterprises (SOEs) by AKN VII of the Audit Board of the Republic of Indonesia. Sustainable energy development, focused on renewable energy and energy efficiency, is a key priority in the 2020–2024 Medium-Term National Development Plan. Given SOEs' significant role in implementing this program, auditing their performance and governance is essential to achieving national strategic goals. The Integrated Audit Approach addresses limitations of traditional audits, such as restricted coverage and less strategic recommendations, by combining financial, compliance, and performance audits. This comprehensive method yields more in-depth and sustainable recommendations. The research uses a qualitative, descriptive-exploratory approach, gathering data through interviews with Audit Board auditors and reviews of internal reports and documents. Findings indicate that the integrated audit approach enhances SOEs' audit quality by delivering more strategic and relevant recommendations, particularly in sustainable energy governance. This study aims to advance audit theory and practice within the Audit Board, contributing to improved governance and performance of SOEs.